ЕФЕКТИВНІСТЬ ЗАСТОСУВАННЯ АСИНХРОННОГО ДВИГУНА З СУЦІЛЬНИМ ОСЕРДЯМ ЗАНУРЕНОГО СВЕРДЛОВИННОГО НАСОСУ ЗА ЗБІЛЬШЕНОЇ ЧАСТОТИ ЖИВЛЕННЯ - Головань, І.В.; Попович, О.М.; Шевчук, С.П. (Інститут електродинаміки НАН України, Київ, 2026)
The article presents the results of the optimization-based parametric synthesis of an induction motor with a solid core for a submersible borehole pump operating at doubled supply frequency. The proposed synthesis methodology is based on a weakly coupled circuit-field mathematical model with iterative parameterization of field analysis results. This approach makes it possible to account for nonlinear magnetic properties, rotor-induced currents, additional losses in the solid ferromagnetic rotor, and the interaction of all elements of the electromechanical system. According to the criterion of maximum efficiency, the optimal values of the variable design parameters of the induction motor with a solid core for the submersible borehole pump were determined, taking into account the load magnitude at supply frequencies of 50 and 100 Hz. The results demonstrate a significant improvement in system performance: a 2.2-fold increase in water lifting capacity, a 4% increase in motor efficiency, a 1.9-fold reduction in the payback period of the borehole, and a threefold reduction in the number of impellers in the pump. Design solutions are substantiated for the induction motor with a solid rotor-shaft and a dismountable stator made of powder material with closed slots, which contribute to reducing copper, steel, and fluid losses. The proposed technical solutions lay the groundwork for designing optimized electromechanical systems for submersible borehole pumps with improved capital and operational cost indicators. References 20, figures 3, tables 2.